INALIENABLE POSSESSION IN SWEDISH AND DANISH – A DIACHRONIC PERSPECTIVE - Piotrowska, Alicja; Skrzypek, Dominika (Folia Scandinavica Posnaniensia, 2017)
In this paper we discuss the alienability splits in two Mainland Scandinavian languages, Swedish and Danish, in a diachronic context. Although it is not universally acknowledged that such splits exist in modern Scandinavian languages, many nouns typically included in inalienable structures such as kinship terms, body part nouns and nouns describing culturally important items show different behaviour from those considered alienable. The differences involve the use of (reflexive) possessive pronouns vs. the definite article, which differentiates the Scandinavian languages from e.g. English. As the definite article is a relatively new arrival in the Scandinavian languages, we look at when the modern pattern could have evolved by a close examination of possessive structures with potential inalienables in Old Swedish and Old Danish. Our results reveal that to begin with, inalienables are usually bare nouns and come to be marked with the definite article in the course of its grammaticalization.